Processing-Structure-Properties Relationships in Polymers - Pantani, Roberto (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This collection of research and review papers is aimed at depicting the state of the art on the possible correlations between processing variables, obtained structure and special properties which this structure induces on the plastic part. The extraordinary capacity of plastics to modify their properties according to a particular structure is evidenced for several transformation processes and for many applications. The final common goal is to take profit of this peculiar capacity of plastics by inducing, through a suitable processing, a specific spatial organization.